TREATMENT OF DERMATOPHYTE ONYCHOMYCOSIS WITH TERBINAFINE (LAMISIL) PULSE THERAPY - Sonia Valkova (Peytchinski Publishing, 2004)
Terbinafine is the most active currently available antidermatophyte agent with fungicidal action. The aim of the present study was to assess the efficacy of terbinafine pulse therapy in the treatment of dermatophyte nail infections. Seven patients (two with fingernail, four with toenail and one with mixed onychomycosis) have been treated with 500 mg terbinafine daily for one week per month. The duration of the treatment was four months for toenail and three months for fingernail onychomycosis. At the end of the follow-up period (six months after discontinuation of treatment) 6 out of 7 patients (87%) were mycologically cured. In conclusion, pulse terbinafine therapy is an effective regimen for the treatment of dermatophyte nail infections.